PENGARUH KONSEP DIRI DAN PENGEMBANGAN KEPRIBADIAN TERHADAP PRESTASI KERJA KARYAWAN TVRI STASIUN SURABAYA ( BAGIAN PROGRAM ) - Sulistiyowati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2016)
The main problem discussed in this paper is whether there is a positive influence self concept and development of the personality on employee performance Stasin TVRI Surabaya (Part Program). To solve the problems discussed authors use data analysis method is multiple linear regression analysis were preceded by calculating the average of each variable. And before should be done beforehand regression analysis instrument to be tested for validity and reliability. The analysis shows that the authors have found show that : 1) partially self-concept and personality development is partially significant effect on the performance of TVRI Surabaya Employees (Part Program). 2) simultaneously the concept of self and personality development affect the work performance of employees TVRI Surabaya (Part Program). 3) Variable kansep self is the dominant variable effect on employee job performance TVRI Surabaya (Part Program).